Psychosocial Counseling for Human Trafficking in Palangka Raya - Gusti Rahma Nurhaifa; Nor Fatmah (Al-DYAS, 2026)
This community-service study examines the role of psychosocial counseling in supporting the psychological and social recovery of women involved in commercial sex work (CSW) linked to human trafficking in Indonesia. Using a participatory and trauma-informed design, trained counselors implemented a needs-based program integrating individual trauma-focused cognitive behavioral therapy, brief psychosocial stabilization, coping-skills training, and rights-literacy awareness, accompanied by referrals to legal, health, and social-protection services. Participants were identified through partner coordination and screened for psychosocial needs, while outcomes were monitored through session notes, pre–post brief instruments, satisfaction evaluations, and follow-up activities. A case subject, a widowed single mother who entered CSW due to post-divorce economic pressure and limited social support, illustrates the structural drivers of vulnerability, including poverty, social isolation, and informal recruitment, as well as multilayered harms such as shame, guilt, anxiety, emotional suppression, and somatic complaints. The findings indicate that counseling fostered empathetic therapeutic relationships, emotional validation, psychoeducation, and practical coping techniques, resulting in reduced emotional suppression, greater openness, improved coping capacity, emerging hope, and initial planning toward safer livelihoods. However, the findings also show that trauma-informed psychosocial counseling, while contributing meaningful short-term psychosocial gains, is insufficient as a standalone intervention. Durable recovery requires integrated responses that address structural determinants, including economic alternatives, confidential welfare access, and coordinated multi-sector referrals. This study contributes to victim recovery and community-based psychosocial intervention literature by highlighting the importance of embedding counseling within gender-sensitive, trauma-oriented service models. Larger-sample evaluations using standardized measures and longer follow-up are needed to assess the effectiveness and cost-effectiveness of combined psychosocial and structural interventions.